Analisis Gangguan Static Frequency Converter (SFC) PLTG Gilimanuk - Reza Adisetia Saputra; I Wayan Sugara yasa; I Nyoman Gede Adrama (Jurnal Ilmiah Telsinas, 2020)
The electricity system in Bali is supported by several generators, including PLTD / G Pesanggaran, PLTG Gilimanuk, PLTG Pemaron, Sea Cables and IPP Generators in meeting electricity needs in Bali, which can supply electricity needs at the greatest peak load of 940 MW. Along with the increasing various types of electricity consumers in Bali, the performance of each operation is demanded to be in prime condition.However, it does not rule out the disturbance will occur over time, among others, at the Gilimanuk PLTG, an SFC interruption with Card Processor Error Indication and, the Gilimanuk PLTG unit failed to start with an indication on the HMI SSD N. Alarm caused by damage to the 24VDC "traco power switching supply module". PLTG Gilimanuk Simple Cycle ABB 13E2 uses Static Frequency Converter (SFC) as the initial mover by turning the generator into a motor to rotate the turbine to 85% speed. With a disturbance in the processor module it resulted in a failure to start the GT Gilimanuk. Root Cause Analysis tool which is quite easy to do to help find the root of the problem or cause and effect in dealing with future problems. One way to do this is by using the FMEA (Failure Mode and Effects Analysis) tool, Fish Bone Analysis and Fault Tree Analysis.